The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1519/jsc.0b013e31816eb46a
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Strength Changes From Resistance Exercise and Albuterol on Unloaded Muscle

Abstract: To assess unloaded knee extensor temporal strength changes, healthy subjects without asthma performed 40 continuous days of unilateral limb suspension, whereby their left leg refrained from normal weight-bearing and ambulatory activity. During the 40-day period, subjects performed resistance exercise (REX) with their unloaded leg on an inertial resistance ergometer and, as part of a double-blind design, consumed the maximal oral therapeutic dosage of albuterol (i.e., 16 mg.d) or a placebo (i.e., lactose) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Le Panse et al did employ DXA scanning during 3‐4 weeks of oral salbutamol ingestion (12 mg/d), but employed a cross‐over design, which makes small changes in lean mass difficult to detect, as subjects who started with the salbutamol treatment most likely did not revert to baseline lean mass in the 4‐week washout period . In addition, studies that examined effects of salbutamol on body composition used self‐reported records as a measure of drug compliance, and lack of observed effects of salbutamol may therefore be attributed to low drug adherence. Indeed, studies show low drug compliance when relying on self‐reported records, being as low as 50% when the study drug is to be taken several times daily, as was the case for these studies .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Le Panse et al did employ DXA scanning during 3‐4 weeks of oral salbutamol ingestion (12 mg/d), but employed a cross‐over design, which makes small changes in lean mass difficult to detect, as subjects who started with the salbutamol treatment most likely did not revert to baseline lean mass in the 4‐week washout period . In addition, studies that examined effects of salbutamol on body composition used self‐reported records as a measure of drug compliance, and lack of observed effects of salbutamol may therefore be attributed to low drug adherence. Indeed, studies show low drug compliance when relying on self‐reported records, being as low as 50% when the study drug is to be taken several times daily, as was the case for these studies .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies that examined effects of salbutamol on body composition used self‐reported records as a measure of drug compliance, and lack of observed effects of salbutamol may therefore be attributed to low drug adherence. Indeed, studies show low drug compliance when relying on self‐reported records, being as low as 50% when the study drug is to be taken several times daily, as was the case for these studies . In addition, side effects associated with beta 2 ‐agonists may be unpleasant, and participants may deviate from the dosing regimen they were asked to follow .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, beta 2 ‐adrenergic‐induced changes in trueV˙O 2max and muscle oxidative enzymes may be confounded by particular types of training. Furthermore, in spite of the studies on the beta 2 ‐adrenergic effects on muscle strength in response to resistance training, no studies have, to our best knowledge, investigated whether concurrent resistance training affects adaptations in absolute and relative trueV˙O 2max as well as in muscle oxidative enzymes in response to chronic beta 2 ‐adrenergic agonist treatment. As such, while absolute trueV˙O 2max may be unaltered by chronic beta 2 ‐adrenergic agonist treatment, their hypertrophic effect may compromise trueV˙O 2max relative to body mass or lean mass.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the present study also showed a significant main effect of gender in aerobic performance, with lower estimated VO 2max values in active female than male athletes after the MFST. In contrast, during supra‐maximal exercise after salbutamol intake (3‐4 weeks, 12 mg daily), some studies showed no potentiating effects of gender (Caruso et al, 2008; Le Panse et al, 2005). In addition, no significant differences were observed between males and females in both groups for RPE value in the current study.…”
Section: Discussionmentioning
confidence: 97%